Decision Support System for Identifying Technical Condition of Combustion Engine - DEPTUŁA, Adam; OSIŃSKI, Piotr; RADZIWANOWSKA, Urszula (Archives of Acoustics, 2016)
The paper is a continuation of the publication under the title “Acoustic diagnostics applications in the study of technical condition of combustion engine” and concerns the detailed description of decision support system for identifying technical condition (type of failure) of specified combustion engine. The input data were measured sound pressure levels of specific faults in comparison to the noise generated by undamaged motor. In the article, the whole procedure of decision method based on game graphs is described, as well as the interface of the program for direct usage.